Training Bilingual Inquiry-Based Mathematics Games for Teachers and Students at SDN 1 Taji Malang - Rahayu, Widya Adhariyanty; Subekti, Puji; Nuryana, Ida (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service program aimed to improve the quality of mathematics ang English learning at SDN 1 Taji, a rural elementary school in Malang Regency with limited access to technology and innovative media. The intervention addressed low teacher capacity in applying inquiry-based methods and low student motivation in learning mathematics and English. Method: The program involved training teachers, mentoring in lesson plan design, and implementing an inquiry-based bilingual mathematics board game in classrooms. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using descriptive qualitative and quantitative approaches. Practical Applications: The results indicated that teachers became more motivated and skilled in interactive instruction, while students showed greater enthusiasm, active participation, and improved conceptual understanding. The bilingual elements also supported contextual English literacy. Conclusion: The program provided a resource-efficient, replicable, and sustainable model for enhancing mathematics and English learning in rural schools, contributing to educational innovation in under-resourced contexts.